Monkeewrench - Tracy, P. J. (Tracy, P. J. Monkeewrench novel., 2003)
The slaying of an old couple in smalltown America looks like a one-off act of retribution. But at the same time, in Minneapolis, teams of detectives scramble to stop a sickeningly inventive serial killer striking again. The two investigations converge on an isolated Catholic boarding school.